(untitled) (Journal of the College of Basic Education, 2025)
Abstract: The aim of the current research is to identify the effect of the logical-mathematical intelligence strategy on developing mathematical thinking skills among students in the Mathematics Department at the College of Basic Education. To achieve the research objective, the researcher used the experimental method, a quasi-experimental design. The research sample was intentionally selected from first-year students in the Mathematics Department at the College of Basic Education / Al-Mustansiriya University, within the morning study, numbering (149) male and female students, from which (69) male and female students were randomly selected. After excluding absent, failed, and completed students in the number theory course, the sample was divided into two groups, one of which is the experimental group, which is from Section B, numbering (34) male and female students, which is taught using the logical-mathematical intelligence strategy. The other is an officer, and they are from Section C, numbering (35) male and female students, who are taught using the regular method. The researcher also prepared a test to measure mathematical thinking skills. She relied on (6 skills) in constructing the test: (logical thinking, inference, generalization, abstraction, problem solving, mathematical communication). The test consists of (20) paragraphs, formulated in the form of objective paragraphs (multiple choice). One mark was given to each paragraph of the test. Each paragraph consists of four alternatives, only one of which is correct. An answer form was prepared for each paragraph of the test, as the total mark for the mathematical thinking skills test was (20) marks. Its validity was confirmed by presenting it to a group of arbitrators, and extracting the difficulty and discrimination coefficient. For its paragraphs, and extracting the Kuder-Richardson equation (KR-20), the overall reliability coefficient of the test reached (0.76), which is a good value, and the reliability coefficients were extracted for each skill of the test skills, and after the end of the experiment, the test was applied to the two research groups. The final data was processed statistically using the Statistical Program for Social Sciences (SPSS) version 22. The results indicated the following: - The effect of the logical-mathematical intelligence strategy in developing mathematical thinking skills among students of the Mathematics Department at the College of Basic Education, as it led to a general improvement in each of the thinking skills. The mathematical abilities of the experimental group that used the strategy. In light of these results, the researcher made several proposals and recommendations, including: - Designing a training program based on the logical-mathematical intelligence strategy for teachers in colleges of basic education. - Using the logical-mathematical intelligence strategy in teaching mathematics in colleges of basic education. - Training teachers to use this strategy effectively in teaching mathematics